Professional learning for antiracist district transformation: the role of transformational leadership and double-loop learning - Patricia Marisol Virella; Chedia Ayari; Steve Tozer (Frontiers in Education, 2025)
IntroductionThis study investigates how professional learning contributes to antiracist district transformation, focusing on the roles of transformational leadership and double-loop learning. Transformational leadership inspires followers to achieve exceptional goals, while double-loop learning involves questioning underlying assumptions and values to foster systemic change.MethodsA longitudinal case study approach was employed to examine the experiences of seven district and school-level leaders in an urban-intensive school district. These leaders participated in a multi-year antiracist professional learning series designed to promote equity and systemic change.ResultsPreliminary findings indicate that the professional learning series facilitated a shift in participants’ racial schema and enhanced their capacity to navigate resistance to antiracist practices. For example, leaders implemented new protocols for reviewing instructional materials to ensure cultural relevance and inclusivity. Participants also reported developing strategies to address resistance, such as facilitating open forums to discuss concerns and build consensus.DiscussionThis study contributes to the growing body of literature on leadership for equity, highlighting the importance of professional learning in promoting antiracist transformation. The findings offer insights for districts seeking to foster systemic change and provide practical strategies for leaders navigating resistance to equity initiatives.